Caesarean Section - Georgios Androutsopoulos (IntechOpen, 2018)
In this book, we present recent advances in surgical techniques as well as the most common perioperative complications in patients that undergo a cesarean section. Moreover, we discuss appropriate measures to reduce unnecessary procedures.
English
Keywords: Medicine; Health Sciences; Obstetrics and Gynecology